PEMANFAATAN LINGKUNGAN SEBAGAI LABORATORIUM ALAM PADA PEMBELAJARAN IPA SD - Retno Utaminingsih (Universitas Sarjanawiyata Tamansiswa, 2015)
Â Â This article describes the use of the environment as a natural laboratory in science teaching elementary school. There are many strategies that can be applied in teaching science in elementary schools. One way is to use the environment as a natural laboratory in science teaching in primary school. As the target environment, resource and learning tool can be used as a natural laboratory to practice, demonstrations, experiments, research, and decision science in the process of learning science. By utilizing the environment as a natural laboratory in the process of learning science is expected that students will get information based on direct experience and can learn from the things that are concrete so that students can easily understand the material and learning experienced by students more meaningful.Â